2013
DOI: 10.1016/j.ijmedinf.2013.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Giving patients granular control of personal health information: Using an ethics ‘Points to Consider’ to inform informatics system designers

Abstract: The P2C is intended to clarify what is at stake when designers try to accommodate potentially competing ethical commitments and logistical realities. The P2C was developed to guide informaticists who were designing a query tool in an existing EHR that would permit patient granular control. While consideration of ethical issues is coming to the forefront of medical informatics design and development practices, more reflection is needed to facilitate optimal collaboration between designers and ethicists. This re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 24 publications
0
30
0
Order By: Relevance
“…We have previously published the requirements for capturing patients' preferences for viewing information in their EHRs 19 and an ethics framework for following FIP principles in health care. 20 Articles published elsewhere in this JGIM supplement describe the process of designing the patient preference program, 21 and challenges that had to be overcome to incorporate it into Careweb to control the display of EHR data to clinicians. 22 In this article, we report the results of a demonstration study where we implemented this patientcontrolled EHR access program in a single primary care clinic in Eskenazi Health's large urban primary care network and prospectively assessed its effects on EHR data displays and providers' reactions.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously published the requirements for capturing patients' preferences for viewing information in their EHRs 19 and an ethics framework for following FIP principles in health care. 20 Articles published elsewhere in this JGIM supplement describe the process of designing the patient preference program, 21 and challenges that had to be overcome to incorporate it into Careweb to control the display of EHR data to clinicians. 22 In this article, we report the results of a demonstration study where we implemented this patientcontrolled EHR access program in a single primary care clinic in Eskenazi Health's large urban primary care network and prospectively assessed its effects on EHR data displays and providers' reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings thus re-emphasize the need for any system of granular control to be coupled with an efficient and meaningful system for educating patients on the type of information included in the EHR, who uses it and why and how, and the potential impacts of restricting access to data. 4 Like all studies, our work has limitations that warrant consideration. First, we utilized a simple patient interface for stating choices, and there was no educational intervention regarding the content and use of data in the EHR beyond simply listing types of information that it contains.…”
Section: Discussionmentioning
confidence: 97%
“…Are there situations (e.g., during life-threatening emergencies) where providers should be allowed to override the patients' data-sharing preferences? 4,6 To address these questions, designers of EHRs need a better understanding of patients' perspectives regarding control of personal information. Previous research has investigated patient preference with respect to sharing EHR data with both health care providers (e.g., physicians) and non-provider recipients (e.g., family members).…”
Section: Introductionmentioning
confidence: 99%
“…1 Fully applying Fair Information Practice Principles to electronic health records (EHRs) would require giving patients the ability to control who has access to specific information within their EHRs, which could have a number of important clinical, ethical, and legal consequences. 2 We have previously shown that most patients do desire to have such control over their EHR information but have widely divergent opinions about who should have access and what information they should be able to see. 3 We found that 100 % of patients without sensitive EHR information were willing to provide their primary care physicians (PCPs) with full access to their EHRs, as would 90 % of those with sensitive information.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, clinicians, health system leaders, and patient advocates are also likely to have divergent opinions of the benefits, risks, and impact on patient care from patients' having control over access to their EHRs. 2,4 Although scholars have identified clinical, ethical, and legal challenges in providing patients with control of their EHR data, 2 there is a paucity of literature describing technical approaches to implementing such a policy. Under contract to the National Coordinator for Health Information Technology, we developed and implemented a system for obtaining and following patients' preferences for EHR access.…”
Section: Introductionmentioning
confidence: 99%